Logbook pro doktorský studijní program Speciální pedagogika - Vrubel, Martin (Masaryk University Press, 2021)
Title in English: Logbook for Special Edication Doctoral Program. The LOGBOOK of academic activities is an overview of fulfilled requirements for the course and completion of studies specified in the internal regulations of the faculty, accreditation materials of the study program and the catalog of courses. The logbook of academic activities is a students' document on the activities completed during their studies, which are part of the competencies of the graduates of the doctoral study program Special Education. The logbook functions as a control and feedback tool for students and supervisors regarding their completed activities.